Theory and treatment planning in counseling and psychotherapy - Gehart, Diane R., 1969- (Cengage, 2015)
Introduces counseling and psychotherapy theories using theory-informed case conceptualization as well as treatment planning.
Includes bibliographical references and indexes.
Keywords: Counseling -- Planning; Psychotherapy -- Planning; Counseling -- Study and teaching; Psychotherapy -- Study and teaching; Mental health counseling; Counseling; Psychotherapy; Psychotherapy